2017
DOI: 10.1080/09638288.2017.1342277
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Regulation in Exercise Questionnaire in people with schizophrenia: construct validity of the Portuguese versions

Abstract: Analyses of version 2 provided an adequate fit index for the structure of the five factors. Exploratory analyses suggested retaining 2 factors of version 3. The results of this study suggest that version 3 was an appropriate measure to assess controlled and autonomous motivation for physical activity in people with schizophrenia and support its use in clinical practice and research. Implications for Rehabilitation This study supports the need to identify the reasons why people with schizophrenia practice physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
2
12
0
1
Order By: Relevance
“…However, it is interesting to note that the Brazilian version of the BREQ2 ( Klaine et al, 2015 ), also validated in a sample of gym exercisers, only adjusted to the data after the elimination of two items (one of intrinsic motivation and one of identified regulation), suggesting inconsistencies in some items. Similar results were found in a recent study carried out with a sample of patients diagnosed with schizophrenia ( Costa et al, 2017 ), who identified problems in the Portuguese version of BREQ-3 structure (i.e., cross-loading between some items of controlled and autonomous motivation, particularly, in introjected and identified regulations), which highlights the need to further develop studies than can improve and refine the use of this scale.…”
Section: Discussionsupporting
confidence: 87%
“…However, it is interesting to note that the Brazilian version of the BREQ2 ( Klaine et al, 2015 ), also validated in a sample of gym exercisers, only adjusted to the data after the elimination of two items (one of intrinsic motivation and one of identified regulation), suggesting inconsistencies in some items. Similar results were found in a recent study carried out with a sample of patients diagnosed with schizophrenia ( Costa et al, 2017 ), who identified problems in the Portuguese version of BREQ-3 structure (i.e., cross-loading between some items of controlled and autonomous motivation, particularly, in introjected and identified regulations), which highlights the need to further develop studies than can improve and refine the use of this scale.…”
Section: Discussionsupporting
confidence: 87%
“…This study, however, presents a broader sample than previously published. Costa et al. (2017) validated a scale that evaluates the six types of behavioral regulation in an exercise context with a sample of 118 individuals with schizophrenia, and Banack, Sabiston, and Bloom (2011) studied coaches' support for autonomy, BPNs, and intrinsic motivation in 130 parasport athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors did not include the integrated regulation subscale because they found that it was not possible to empirically distinguish between integrated and identified regulation, and, due to an error, they omitted one identified regulation item. Previous research has supported the BREQ-2's factor structure and subscale reliability in different languages (e.g., Moreno et al, 2007; Moustaka et al, 2010; Costa et al, 2018).…”
Section: Introductionmentioning
confidence: 87%
“…This new version contains 23 items divided into six subscales: amotivation (four items), external regulation (four items), introjected regulation (four items), identified regulation (three items), integrated regulation (four items), and intrinsic motivation (four items). The BREQ-3 obtained acceptable fit indexes and adequate reliability in different languages (Wilson et al, 2006; González-Cutre et al, 2010; Guedes and Sofiati, 2015; Cid et al, 2018; Costa et al, 2018). Furthermore, several researchers have provided additional support for the BREQ-3 demonstrating that scores on the questionnaire discriminated among male and female groups (e.g., González-Cutre et al, 2010; Guedes and Sofiati, 2015; Su et al, 2015; Cid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%